ANALISIS GAME THEORY PADA STRATEGI BERSAING GRAB DAN GO-JEK DI KABUPATEN KEBUMEN - Windasari, Wahyuni; Zakiyah, Tuti (P4M STIE Putra Bangsa, 2019)
The phenomenon of the presence of online motorcycle taxi services in Kebumen has resulted in competition between Grab and Gojek online transportation service providers in Kebumen. In this research, game theory analysis is used to find out the best strategy that can be used by the two online transportation service providers. This study uses eight marketing attributes, namely practical, cost-effective, safety, comfort, promos, fleet availability, non-cash payments, and completeness of facilities. From the research results it is known that the optimal value is 34. The best strategy used by Grab to obtain maximum profit is the convenience strategy and voucher promo with each proportion of 50%, while for Gojek the strategy used to minimize losses is the cost-effective attribute of 20 % and security attributes at 80%.